From Intrusion Detection to an Intrusion Response System: Fundamentals, Requirements, and Future Directions - Shahid, Anwar; Jasni, Mohamad Zain; Mohamad Fadli, Zolkipli; Inayat, Zakira; Khan, Suleman; Anthony, Bokolo Jnr.; Chang, Victor (MDPI AG, 2017)
In the past few decades, the rise in attacks on communication devices in networks has resulted in a reduction of network functionality, throughput, and performance. To detect and mitigate these network attacks, researchers, academicians, and practitioners developed Intrusion Detection Systems (IDSs) with automatic response systems. The response system is considered an important component of IDS, since without a timely response IDSs may not function properly in countering various attacks, especially on a real-time basis. To respond appropriately, IDSs should select the optimal response option according to the type of network attack. This research study provides a complete survey of IDSs and Intrusion Response Systems (IRSs) on the basis of our in-depth understanding of the response option for different types of network attacks. Knowledge of the path from IDS to IRS can assist network administrators and network staffs in understanding how to tackle different attacks with state-of-the-art technologies.